Prefabricated Composite Graft for Eyelid Reconstruction - Nicoletti, Giovanni; Jaber, Omar; Tresoldi, Marco Mario; Pellegatta, Tommaso; Faga, Angela (Facial Plastic Surgery, 2015)
The authors propose a prefabricated chondromucosal composite graft to reconstruct full-thickness defects of the lower eyelid. The technique was used in a patient suffering from a locally invasive basal cell carcinoma of the lower eyelid, who had previously undergone an extensive submucosal nasal septum resection. One week prior to the eyelid resection, the anterior skin surface of the auricular concha was replaced with a full-thickness oral mucosa graft. One week later, a full-thickness excision of the right lower eyelid was performed and the prefabricated chondromucosal auricular graft was used to restore the posterior lamella. The anterior lamella was reconstructed with a bipedicled myocutaneous flap from the upper eyelid. Because of the patient's scheduling needs, the medial pedicle of the flap was divided 28 days later and the lateral one after further 37 days. All the procedures were performed under local anesthesia. This technique adds a simple key detail to other time-honored reliable techniques, thus outlining an extremely convenient sequence for full-thickness eyelid reconstruction. The easily prepared prefabricated chondromucosal graft might be associated with any of the previously described flaps, thus providing a versatile and reliable method of posterior lamella reconstruction.
Keywords: eyelid reconstruction; prefabricated graft; posterior lamella; chondromucosal; graft; auricular cartilage graft